Population Dynamics of the Fiddler Crab Tubuca rhizophorae (Tweedie, 1950) in the Mekong Delta, Vietnam - Anh Ngoc Tran; Lam Thi Thao Vo; Quang Minh Dinh; Gieo Hoang Phan; Nhien Thi My Huynh; Bang Thi Nhu Le; Ton Huu Duc Nguyen (Ecology and Evolution)
ABSTRACT This study investigates the population characteristics of the fiddler crab, Tubuca rhizophorae, at two sites in the Mekong Delta, Vietnam. Monthly samples were collected from March 2024 to February 2025 in Dong Hai, Bac Lieu and Dam Doi, Ca Mau. Population parameters, including asymptotic carapace width (CW∞ = 23.18 mm), growth rate (K = 0.68/year), longevity (approximately 4.41 years), total mortality (3.22/year), natural mortality (1.55/year), fishing mortality (1.69/year), exploitation rate (0.52/year), and carapace width at first capture (CWc = 13.60 mm), were estimated. The results indicate that the T. rhizophorae population exhibits rapid growth, relatively short longevity, and is subject to significant fishing pressure; the exploitation rate was determined to be 0.52/year, which exceeds the E50 value (0.401). The study also reveals two major annual recruitment peaks occurring at the beginning and end of the year. These findings provide critical baseline data for developing sustainable management strategies for this fiddler crab species, which are crucial for maintaining biodiversity and ecosystem health in the Mekong Delta.